NELAYAN TIKU: TRADISI DAN KELEMBAGAAN SOSIAL BERDASARKAN BUDAYA MASYARAKAT LOKAL BERBASIS KOMUNITAS DALAM AKTIVITAS PENANGKAPAN IKAN - Lucky Zamzami (Universitas Andalas, 2015)
This article based on the results of research conducted at one of the villages the coastal areas of West Sumatra, in Nagari Tiku Selatan, Tanjung Mutiara District, Agam. This area have been based on traditions since ancestors held as tradition